SIMBOL KOMUNIKASI PEDAGANG KELILING DI SIDOSERMO SURABAYA - Pratiwi, Bertharia Sanny; Hamim, Hamim; Wibowo, Judhi Hari (Universitas 17 Agustus 1945 Surabaya, 2018)
This research was motivated by the communication symbol or symbols likethis is very attached to the Indonesian nation and even many people who are not awarethat it was applying the theory of communication in their daily lives. Emblem usefulnessas a tool to influence the communicant, a tool to make someone understand the messagedelivered, the tools to make sense of the messages being delivered, means to connect thecommunicator to the communicant, a tool to achieve a goal of communication. The soundof street vendors around the place we live, with a characteristic sound when the merchantwas around the area where you live to peddle his wares. Pedlar or commonly referred toPKL is the term given to the hawkers who use carts.As for supporting this study, the authors in the manufacture thesis usingqualitative methods deskripstif. Goal authors is that the notion of communication Symboltraders we need to understand more, because a lot of symbols - symbols of merchants thatwe do not understand.Keywords : symbol communication , trader